Peran Satuan Sabhara Melalui Patroli Roda Dua Dalam Rangka Mencegah Tindak Pidana Curanmor Di Wilayah Hukum Kota Cimahi - Ghazi, Muhammad Daffa (Police Studies Review, 2020)
Role of Two Wheel Patrol Unit Sabhara Cimahi Regional Police in preventing motor vehicle theft. Related to this, the purpose of this study is to describe the picture of a criminal case of motor vehicle theft, describe the role of the Two Wheeled Patrol Unit Sabhara Cimahi Police in preventing curanmor and describe the factors that influence why the occurrence of the curanmor and the constraints of the Sabhara Unit itself in preventing curanmor. The theories and concepts used are role theory, management theory, routine activity theory, management element concept, crime prevention strategy concept, and patrol concept. This research, the approach used is qualitative and the method used is analytical descriptive. Data collection techniques used were interviews, direct and documented observations, and study of documents. Furthermore, the data obtained were analyzed by data reduction, data display, and conclusions. The results showed that the crime of motor vehicle theft in the jurisdiction of Cimahi City was included in a prominent crime. Prevention efforts made by the Cimahi Police Sabhara Unit by optimizing the implementation of patrols ranging from patrols, implementation, routes, targets, and vulnerable times. The conclusion of the occurrence of motor vehicle theft is urged by the economic needs of the perpetrators and their ignorance and the unconsciousness of the community towards its own environmental security. The implementation of patrols is also less than optimal due to obstacles such as lack of budget for fueling motor vehicles, and the lack of patrol members. The advice that can be given in this research is the need for better management of Kasat Sabhara himself in carrying out his duties, especially in prevention efforts.